2011
DOI: 10.1186/1475-2875-10-283
|View full text |Cite
|
Sign up to set email alerts
|

In vitro susceptibility to pyrimethamine of DHFR I164L single mutant Plasmodium falciparum

Abstract: BackgroundRecently, Plasmodium falciparum parasites bearing Pfdhfr I164L single mutation were found in Madagascar. These new mutants may challenge the use of antifolates for the intermittent preventive treatment of malaria during pregnancy (IPTp). Assays with transgenic bacteria suggested that I164L parasites have a wild-type phenotype for pyrimethamine but it had to be confirmed by testing the parasites themselves.MethodsThirty Plasmodium falciparum clinical isolates were collected in 2008 in the south-east o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
4
5
1
Order By: Relevance
“…We found a correlation between the dhfr S108N single mutation and pyrimethamine resistance, and a correlation between the dhfr N51I/C59R/S108N triple mutation, as well as the dhfr N51I/C59R/S108N and dhps A437G quadruple mutation, and pyrimethamine resistance. Overall, we found a significant difference in the geometric mean IC 50 values for pyrimethamine ( p = 0.0009) between parasites possessing wild-type and resistant alleles in dhfr , as has been reported by others ( Andriantsoanirina et al, 2011 ). We confirmed the existence of an association between the dhfr genotype and chemosensitivity to pyrimethamine in P. falciparum isolates from Thies, as the increase in the number of mutations was associated with an increase in ex vivo resistance to pyrimethamine, similar to what has been observed in Gabon ( Aubouy et al, 2003 ), Central African Republic ( Menard et al, 2006 ), and Cote D’Ivoire ( Djaman et al, 2007 ).…”
Section: Discussionsupporting
confidence: 87%
“…We found a correlation between the dhfr S108N single mutation and pyrimethamine resistance, and a correlation between the dhfr N51I/C59R/S108N triple mutation, as well as the dhfr N51I/C59R/S108N and dhps A437G quadruple mutation, and pyrimethamine resistance. Overall, we found a significant difference in the geometric mean IC 50 values for pyrimethamine ( p = 0.0009) between parasites possessing wild-type and resistant alleles in dhfr , as has been reported by others ( Andriantsoanirina et al, 2011 ). We confirmed the existence of an association between the dhfr genotype and chemosensitivity to pyrimethamine in P. falciparum isolates from Thies, as the increase in the number of mutations was associated with an increase in ex vivo resistance to pyrimethamine, similar to what has been observed in Gabon ( Aubouy et al, 2003 ), Central African Republic ( Menard et al, 2006 ), and Cote D’Ivoire ( Djaman et al, 2007 ).…”
Section: Discussionsupporting
confidence: 87%
“…The IC 50 concentrations that were obtained in this study are within the range of previously detected in vitro sensitivity profiles. For pyrimethamine, the IC 50 value of 12 n m lies within the range of reported inhibitory concentrations (< 10 to 480 n m ) in different assay types . Also for WR99210, the IC 50 of 0.039 n m was very near to those previously reported for different parasite lines (0.075–0.21 n m ) .…”
Section: Discussionsupporting
confidence: 82%
“…The results of this study showed a similar pattern with the exception of an absence of mutation in codon N51I. It was observed the I164L mutation associated with high levels of pyrimethamine resistance [21]. Previous studies in Assam, in north-east India and Odisha in eastern India, documented the dhfr triple mutant Asn108 + Ile51 + Arg59 associated with pyrimethamine resistance [17].…”
Section: Discussionsupporting
confidence: 80%